Chlorobenzenes and organochlorinated pesticides in vegetable soils from an industrial site, China - Song, Yang; Wang, Fang; Bian, Yongrong; Zhang, Yinping; Jiang, Xin (Journal of environmental sciences (China), 2012)
Organochlorinated compounds are ubiquitous contaminants in the environment, especially in industrial sites. The objective of the work was to investigate whether a vegetable field near an industrial site is safe for vegetable production. The residues of chlorobenzenes (CBs), hexachlorocyclohexanes (HCHs) and dichlorodiphenyltrichloroethanes (DDTs) in a vegetable field which was near a chemical plant in China were characterized. Point estimate quotient was used for ecological risk assessment of the investigated site. The results showed that all CBs except monochlorobenzene (MCB) were detected in soils. The total concentrations of ∑CBs ranged from 71.06 to 716.57 ng/g, with a mean concentration of 434.93 ng/g. The main components of CBs in soil samples were dichlorobenzenes (DCBs), trichlorobenzenes (TCBs) and tetrachlorobenzenes (TeCBs), while for single congeners, 1,2,4-TCB had the highest concentration, which ranged from 13.21 to 210.35 ng/g with a mean concentration of 111.89 ng/g. Residues of hexachlorobenzene (HCB) in soil samples ranged from 0.9 to 11.79 ng/g, significantly lower than ∑DCB, ∑TCB and ∑TeCB. Concentrations of ∑HCHs and ∑DDTs in soils ranged from 11.32 to 55.24 ng/g and from 195.63 to 465.58 ng/g, respectively, of which the main components were a-HCH and p,p'-dichlorodiphenyldichloroethylene (p,p'-DDE). Ecological risk assessment for the investigated site showed that the most potential risks were from TCBs and TeCBs, based on the hazard quotients. The higher residues of CBs and DDTs compared to the target values and the higher than 1 hazard quotients indicated that this area is not safe for vegetable production and thus soil remediation is needed.